The role of selection in driving landscape genomic structure of the waterflea Daphnia magna. Issue 3 (23rd November 2012) - Orsini, Luisa; Mergeay, Joachim; Vanoverbeke, Joost; De Meester, Luc
Abstract: The combined analysis of neutral and adaptive genetic variation is crucial to reconstruct the processes driving population genetic structure in the wild. However, such combined analysis is challenging because of the complex interaction among neutral and selective processes in the landscape. Overcoming this level of complexity requires an unbiased search for the evidence of selection in the genomes of populations sampled from their natural habitats and the identification of demographic processes that lead to present‐day populations' genetic structure. Ecological model species with a suite of genomic tools and well‐understood ecologies are best suited to resolve this complexity and elucidate the role of selective and demographic processes in the landscape genomic structure of natural populations. Here we investigate the water flea Daphnia magna, an emerging model system in genomics and a renowned ecological model system. We infer past and recent demographic processes by contrasting patterns of local and regional neutral genetic diversity at markers with different mutation rates. We assess the role of the environment in driving genetic variation in our study system by identifying correlates between biotic and abiotic variables naturally occurring in the landscape and patterns of neutral and adaptive genetic variation. Our results indicate that selection plays a major role in determining the population genomic structure of D. magna . First, environmental selection directly impacts genetic variation at loci hitchhiking with genes under selection. Second, priority effects enhanced by local genetic adaptation (cf. monopolization) affect neutral genetic variation by reducing gene flow among populations and genetic diversity within populations.